Division Method and Seepage Law of Seepage Channels in a Tight Reservoir. (29th October 2021) - Wu, Zhenkai; Fang, Feifei; Li, Xizhe; Xiao, Hanmin; Liu, Xuewei; Rao, Yuan; Li, Yang; Wang, Jie; Luo, Yongcheng; Li, Zhi
Abstract : Tight oil reservoirs are characterized by a low porosity, low permeability, and strong heterogeneity. The macropores, throats, and microcracks in reservoirs are the main seepage channels, which affect the seepage law in the reservoirs. In particular, oil-water two-phase flow in different types of pores requires further study. In this study, two groups of online NMR displacement experiments were designed to study the seepage characteristics of tight oil reservoirs. It was found that the main seepage channels for oil-water two-phase flow are the microcracks, large pores, and throats in the reservoir. The large pores are mainly micron and submicron scale in size. The oil in the small pores is only transferred to the large pores through imbibition to participate in the flow, and there is no two-phase flow. Based on the influence of different pore structures on the seepage law of a tight reservoir, the pores were divided into seepage zones, and a multistage seepage model for tight reservoirs was established. Based on this model, the effects of the imbibition, stress sensitivity, threshold pressure gradient, and Jamin effect on model's yield were studied. The results show that imbibition is no longer effective after a while. Owing to the stress sensitivity, the threshold pressure gradient, and the Jamin effect, oil production will be reduced. As the parameter value increases, the oil production decreases. The production decreases rapidly in the early stage of mining while decreases slowly in the later stage, exhibiting a trend of high yield in the early stage and stable yield in the later stage.